2012
DOI: 10.5114/aoms.2012.32417
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the DNA repair genes RAD51 and XRCC2 in smoking- and drinking-related laryngeal cancer in a Polish population

Abstract: IntroductionCigarette smoke and alcohol can generate reactive oxygen species, which may induce DNA double-strand breaks (DSBs), the most serious DNA lesion. In humans, DSBs are repaired mainly by non-homologous end joining and homologous recombination repair (HRR). Several polymorphisms in the DNA repair gene have been extensively studied in the association with various human cancers. In the present work we investigated the association between polymorphisms of two HRR genes, XRCC2 and RAD51, and tobacco- and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…The incidence of cancer of the larynx also has statistical differences according to age and sex (Wunsch, 2004;de Souza et al, 2011), geographical features of the place of residence (Dykhno et al, 2002;Saurina et al, 2010), social class and the living standards of the studied group of population (Vassileiou et al, 2012) and a number of other external factors (Wong et al, 1993;Grant, 2012;Romanowicz-Makowska et al, 2012). In Kazakhstan, it has already been shown that there is geographical variation in incidences of breast (Bilyalova et al, 2012), esophageal (Igissinov S et al, 2012;2013), and cervical cancer , with changes dover time (Igissinov et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of cancer of the larynx also has statistical differences according to age and sex (Wunsch, 2004;de Souza et al, 2011), geographical features of the place of residence (Dykhno et al, 2002;Saurina et al, 2010), social class and the living standards of the studied group of population (Vassileiou et al, 2012) and a number of other external factors (Wong et al, 1993;Grant, 2012;Romanowicz-Makowska et al, 2012). In Kazakhstan, it has already been shown that there is geographical variation in incidences of breast (Bilyalova et al, 2012), esophageal (Igissinov S et al, 2012;2013), and cervical cancer , with changes dover time (Igissinov et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has already been proven that XRCC2 -41657C/ T polymorphism is associated with increased risk of oesophageal squamous cell carcinoma (ESCC), gastric cardia adenocarcinoma (GCA) and smoking-and drinking-related laryngeal cancer [11,16]. However, the functional consequences of -41657C/T XRCC2 polymorphism in the response to different DNA damaging agents still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports provide proof that the XRCC2 -41657C/T genotype was related to increased risk of oesophageal squamous cell carcinoma (ESCC), gastric cardia adenocarcinoma (GCA) and of smoking-and drinking-related laryngeal cancer [11,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanism underlying the development of LC is still poorly understood. Many studies have shown that a defective DNA repair mechanism, impaired cell cycle and aberrant expression of the metalloproteinases might increase the risk of LC occurrence [3,4,5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%